Fe, Co, Ni nanocrystals encapsulated in nitrogen-doped carbon nanotubes as Fenton-like catalysts for organic pollutant removal - Yao, Y.; Chen, H.; Lian, C.; Wei, F.; Zhang, D.; Wu, G.; Chen, B.; Wang, Shaobin (Elsevier BV, 2016)
© 2016 Elsevier B.V. Magnetic metal M (M = Fe, Co, Ni) nanocrystals encapsulated in nitrogen-doped carbon nanotubes (MatN-C) were fabricated conveniently using dicyandiamide as a C/N precursor, and exhibited varying activities toward Fenton-like reaction. The surface morphology and structure of the MatN-C catalysts were characterized and an efficient catalytic degradation performance, high stability, and excellent reusability were observed. In addition, several operational factors, such as initial dye concentration, oxidant type (peroxymonosulfate, peroxydisulfate and H2O2) and dosage, reaction temperature, and dye type as well as stability of the composite were extensively evaluated in view of the practical applications. The results showed that various transition metals M significantly affected the structures and performances of the catalysts, and specially, their activity followed the order of Co > Fe > Ni in the presence of peroxymonosulfate. Moreover, HO and SO4- radicals participating in the process were evidenced using quenching experiments, and a rational mechanism was proposed based on a non-radical process and the free radical process. Control experiments revealed that the enhanced active sites were mainly ascribed to the synergistic effects between the metal nanocrystals and nitrogen-doped carbon. The findings of this study elucidated that encapsulation of nanocrystals in nitrogen-doped carbon nanotubes was an effective strategy to enhance the overall catalytic activity.